Promotion of Bone Lesions Through the Myeloma Integrin α6-Mediated Osteolytic Signaling - Liu, Huan; Wang, Zhiming; He, Jin; Li, Zongwei; Gao, Jerry Y.; Liu, Rui; Lin, Pei; Yang, Jing (Frontiers in Oncology, 2021)
Osteolytic destruction is a hallmark of multiple myeloma and impairs myeloma patients’ quality of life. However, the molecular mechanism underlying the pathogenesis of myeloma-associated bone disease remains unclear. In this study, we demonstrate the role of myeloma cell-expressed integrin α6 in bone. Integrin α6 binds to laminin 8 and epidermal growth factor receptor on mesenchymal stem cells (MSCs) to form a trimer complex and upregulates the secretion of osteolytic cytokines from both myeloma cells and MSCs, leading to enhanced bone resorption and reduced bone formation. Thus, this study elucidates an important mechanism for myeloma-induced bone lesions and implicates that targeting integrin α6 may be a viable approach for bone healing in myeloma patients.